1998
DOI: 10.1088/0031-9155/43/5/024
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Monte Carlo codes EGS4 and MCNP have been compared when calculating radiotherapy depth doses in water. The aims of the work were to study (i) the differences between calculated depth doses in water for a range of monoenergetic photon energies and (ii) the relative efficiency of the two codes for different electron transport energy cut-offs. The depth doses from the two codes agree with each other within the statistical uncertainties of the calculations (1-2%). The relative depth doses also agree with data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Interesting enough, good accordance between the ITS mode of MCNP and EGS4 even with 90 Y has been already been demonstrated. 26,34 Moreover, the authors want to stress two points: First 90 Y is the only nuclide where MIRD 17 and our study disapprove considerably. Secondly, the 90 Y data provided in MIRD 17 differ from all other kernels provided by MIRD and our study in terms of the general behavior of the curve.…”
Section: Resultsmentioning
confidence: 77%
“…Interesting enough, good accordance between the ITS mode of MCNP and EGS4 even with 90 Y has been already been demonstrated. 26,34 Moreover, the authors want to stress two points: First 90 Y is the only nuclide where MIRD 17 and our study disapprove considerably. Secondly, the 90 Y data provided in MIRD 17 differ from all other kernels provided by MIRD and our study in terms of the general behavior of the curve.…”
Section: Resultsmentioning
confidence: 77%
“…MCNP is commonly used for simulating the electron and photon transport in radiotherapy applications. Validation studies (see, e.g., Love et al 1998, Jeraj et al 1999, Chibani and Li 2002 have shown that a good agreement between dose measurements in tissue-equivalent materials and dose distributions computed with MCNP can be achieved when applying the ITS-style algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Three of the most important issues affecting the absorbed dose estimates are briefly presented below, as these points have already been studied and pointed out before. [16][17][18][19][20][21][22]…”
Section: Iia the Mcnp Codementioning
confidence: 99%